EFFECT OF FYM, PHOSPHORUS AND SULPHUR ON YIELD OF SUMEER BLACKGRAM AND POST HARVEST NUTRIENT STATUS OF SOIL - J. M. KOKANI; K. A. SHAH; B. M. TANDEL; G. J. BHIMANI (The Bioscan, 2015)
An experiment conducted to study the “effect of farm yard manure, phosphorus and sulphur on yield of summer blackgram and post harvest status of nutrients under South Gujarat condition at college farm, Navsari Agricultural University, Navsari during summer 2013.” Plant height at 60 DAS and harvest, number of branches, seed (1149 kg/ha) and stover (2652 kg/ha) yields of blackgram were recorded significantly higher under the incorporation of 5 t FYM/ha over control. The protein content, protein yield, organic carbon content, available nitrogen and phosphorus status of soil were also found significantly higher under same treatment. Phosphorus applied @ 40 kg/ha was recorded significantly superior plant height at 60 DAS and harvest, number of branches, number of pods/ plant, number of seeds/ pod, length of pod, grain (1171 kg/ha) and stover (2667 kg/ha) yields as well as protein yield (232.10 kg/ha) of blackgram and available phosphorus in soil (41.97 kg/ha) over control. Significantly the higher plant height at 60 DAS and harvest, number of branches/plant, number of pods/ plant, seeds/ pod, grain (1153 kg/ha), stover (2548 kg/ha) as well as protein yield of blakcgram and available S (21.63 ppm) in soil were observed under 20 kg S/ha compared to control.